Pengaruh Desa Wisata terhadap Perubahan Penggunaan Lahan di Desa Sedit Kabupaten Bangli - Wira Pratami, Ida Rayta (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 5 No 2 (2018): October 2018DO - 10.24843/JRS.2018.v05.i02.p05, 2018)
Government Regulation Number 16 Year 2014 of Bangli Regency in Bali stipulates that Sedit Village is among the 22 communities within this region, which are planned to be community-based tourist destinations. As is often to be the case, such a policy heavily aspires to boost the economy of all parties involved, at all different levels. This is also aim at reducing the rate of people migrating out the village and entering into the city for economic reason. However, when such a development is not well thought, it generates problems that likely cost greater than economic benefits it harvests. Contextualizing its focus on this circumstance, the article discusses impacts of the tourist industry on land development and utilization. It employs a mixed of both qualitative and quantitative research methods relying on data acquired from respondents when interviews are conducted and questionnaires are distributed. Study results corroborate the current trend of development in many developing countries in which a short-term economic gain defeats social and environmental interests, as it also takes place within the development of Sedit Village as a community-based tourism. Several relevant cases pertaining to land use changes are presented within to substantiate this assertion. Prominent among the exhibited instances is an awakening speed of paddy field conversions into numerous commercial uses to support the tourist industry. Since rice farming remains a major form of subsistence for the village, such a condition will ideally have to be taken into account, before it is too late.  Keywords : impact, community-based tourism, land use change, Sedit Village